A REGIONAL-SCALE ROCK GLACIER INVENTORY IN TRENTINO(ITALIAN ALPS) - SEPPI R.; ZUMIANI M.; DALL'AMICO M.; ZAMPEDRI G.; RIGON R.; CARTON, ALBERTO (2011)
A number of rock glacier inventories were implemented in the framework of PermaNET (Permafrost long-term monitoring network), a project part of the European Territorial Cooperation and co-funded by the European Regional Development Fund (ERDF) in the scope of the Alpine Space Programme (www.alpine-space.eu). Rock glaciers are regarded as one of the most prominent permafrost-related landforms in the alpine territories. A new statistical model and a permafrost distribution map for the entire Alps are partly based on the rock glacier inventories carried out within the project and, in this framework, a new inventory was completed also in the province of Trento. This region is located in the southern part of the Alps and 20% of its territory lies above an altitude of 2000 m a.s.l. The rock glacier inventory is based on analyses carried out in a GIS using a recent (2006) orthophoto (resolution of 0.5m) and a DEM (grid resolution of 2m). First, the rock glaciers were identified using i) the orthophotos and ii) an hillshade derived from the DEM. Then, the outline of the landforms were digitized in the GIS as polygon shapes. The characteristics of the rock glaciers were included in an attribute table linked to the shapes. Our database consist of several descriptive parameters, including that of the Permafrost Evidences Database (PED) of the PermaNET project. However, in agreement with other project partner (e.g. ARPA Valle d'Aosta), we used a number of supplementary parameters, in order to achieve a more complete description of the landforms. The database was partially filled in during the landform digitalization, but most of the information (particularly the morphometric parameters) were obtained from analyses performed in the GIS. In summary, a first group of descriptive parameters of each rock glacier include: location (mountain group and coordinates), altitude (mean and range), slope, length, width, perimeter and area. Other parameters describe additional characteristics, such as: geometry (lobate or tongue shape); ...